Long-Term Impact of Toxoplasma gondii Infection on Human Monocytes - Ehmen, Hauke G.; Lüder, Carsten G. K. (Frontiers in Cellular and Infection Microbiology, 2019)
Toxoplasma gondii is a prevalent parasite of mammals and birds including up to 30% of humans world-wide. Primary infection of immunocompetent hosts leads to a robust cell-mediated immune response, which controls but does not clear the infection, thus enabling long-term parasite persistence in brain and muscle tissues. Chronic toxoplasmosis in mice is associated with resistance to heterologous pathogens and this has been related to increased numbers of inflammatory monocytes. Here we have analyzed whether chronic T. gondii infection impacts the subset distribution and the phenotype of peripheral human monocytes in vivo and their responses to parasite infection in vitro. CD14+ monocytes from T. gondii-seropositive blood donors expressed significantly less FcγRIII (CD16) than those from seronegative controls, but they did not show a shift in the distribution of classical, intermediate and non-classical monocyte subpopulations. Percentages of CD62L+ and CD64+ monocytes were however decreased and increased, respectively, in chronically infected individuals as compared to naïve controls. Infection of monocyte-enriched PBMCs from both seropositive and seronegative individuals with T. gondii led to an increase of CD14+ CD16-classical monocytes and a decrease of CD14+CD16+ double positive monocytes. Remarkably, after in vitro parasite infection, expression of the chemokine receptor CCR2 was severely impaired in monocytes from both, individuals with chronic toxoplasmosis and seronegative controls. In contrast, only monocytes from chronically infected humans but not those from controls dose-dependently up-regulated HLA-DR, DP, DQ expression following in vitro infection. Furthermore, monocyte-enriched PBMCs from seropositive individuals up-regulated IL-12 mRNA more vigorously after in vitro infection than cells from naïve controls. Collectively, our results establish that infection of humans with T. gondii exerts long-term effects on the phenotype and responsiveness of blood monocytes. This may have important implications for innate immune responses to T. gondii and unrelated pathogens.